THE DEVELOPMENT STRATEGY OF FASHARKAN LANTAMAL IX XYZ FROM CLASS C FASHARKAN TYPE TO FASHARKAN CLASS A KOARMADA III WITH DELPHI, TOWS AND ISM APPROACH - R Fajar Antariksa; Udisubakti Cipto Mulyono; Sutrisno Sutrisno; Anton Nugroho (JOURNAL ASRO, 2021)
The formation of Koarmada III resulted in a shift and an increase in the number of KRIs in its working area, so that it had to be balanced with the ability of maintenance and repair facilities (fasharkan). Fasharkan XYZ is a fasharkan with class C status so it needs to be upgraded to class A to support KRI improvements. The purpose of this study is to determine an alternative strategy for the development of Fasharkan XYZ with the Delphi approach, TOWS analysis and Interpretative Structural Modeling (ISM). Delphi technique to determine criteria from key factors, TOWS analysis to formulate alternative strategies developed, namely the SO strategy which consists of 7 (seven) strategic steps, the ST strategy consists of 5 (five) strategic steps, the WO strategy consists of 9 (nine) steps strategy and strategy WT consists of 4 (four) strategy steps. From the weighting of the EFE and EFI matrices, the WO strategy is selected. With ISM obtained 5 (five) levels of hierarchical structure from the classification of elements in the WO strategy, namely strategy (WO) 6 at level V. Then sub strategy (WO) 4 is at level IV. At level III it consists of 4 (four) sub strategies, namely (WO) 2; (WO) 3; (WO) 7; (WO) 9. At level II, there are sub strategies (WO) 1 and (WO) 8. At level I sub strategy (WO) 5. Keywords: Fasharkan XYZ, development strategy, Delphi, TOWS, ISM